Histopathological Study of Appendectomy Specimens in a Rural Tertiary Care Hospital in Bangladesh - Rahman, Shamim; Karim, Syeda Noorjahan; Al Tanzim, S M Maruf; Kabir, Evana; Sen, Sampurna; Bristy, Fariha Rahman; Poly, Khaleda Rahman (Mediscope, 2023)
Background: Appendicitis is one of the most common causes of the acute abdomen that demands emergency surgical intervention. It is a clinical condition that is frequently encountered as a diagnostic challenge. Sometimes grossly normal-appearing appendix, removed from patients with suspected acute appendicitis, on histopathological examination may reveal a more serious underlying pathology. Hence, histopathological studies form the gold standard for the diagnosis of appendicitis. Aim: To study the histopathological patterns of appendicitis in patients who underwent appendectomy. Methods: This study was carried out in the department of Pathology, Jahurul Islam Medical College, Bajitpur, Kishoreganj from January 2020 to December 2020. All the appendectomy specimens were received in 10% formalin as fixative. Sections obtained were studied to determine various histopathological patterns in appendectomy specimens. Results: A total of 252 specimens were undertaken for histopathological examination. There were 154 (61.1%) males and 98 (38.1%) females with male to female ratio of 1.6:1. The most common lesion observed was acute appendicitis (51.98%) followed by recurrent appendicitis (28.17%), acute suppurative appendicitis (07.15%), gangrenous appendicitis (06.36%), eosinophilic appendicitis (02.38%), follicular lymphoid hyperplasia (02.38%), mucinous adenoma (0.40%) and mucinous adenocarcinoma (02.38%). Conclusion: Most of the cases in this study were diagnosed with the usual features of appendicitis, though a few of them were incidental diagnoses that were missed clinically. These important incidental diagnoses undisputedly support the notion that every appendectomy specimen must be sent routinely for histopathological examination. Mediscope 2023;10(1): 17-21